2020
DOI: 10.1002/jocc.12166
|View full text |Cite
|
Sign up to set email alerts
|

Storm, Stress, Silence: A Focus Group Examination of Mental Health Culture and Challenges Among Graduate Students Currently or Previously Experiencing Depression

Abstract: The current study explored depression, help-seeking, and academic struggles among graduate students. Focus groups were conducted with graduate students who self-reported currently or previously experiencing depression. Mental health, help-seeking, and campus mental health culture were discussed. Participants described the emergence or reemergence of mental health challenges. Although some reported feeling comfortable discussing depression with friends, participants noted minimal institutional openness about me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Many studies have highlighted the precarious positions that many graduate students find themselves in, as the number of people pursuing doctoral degrees have increased over the years while the number of academic positions decline in intensively competitive neoliberal academic environments and polarising political landscapes (Loher et al, 2019;Nature, 2019;Siegel & Keeler, 2020). Based on a survey of 2279 graduate students (90% Ph.D. and 10% Master's students) from 26 countries Evans et al (2018: 282) found that graduate students were six times more likely to experience anxiety and depression than the general population.…”
Section: Crossing Needles Carrying Yarn---my Fieldwork Storymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have highlighted the precarious positions that many graduate students find themselves in, as the number of people pursuing doctoral degrees have increased over the years while the number of academic positions decline in intensively competitive neoliberal academic environments and polarising political landscapes (Loher et al, 2019;Nature, 2019;Siegel & Keeler, 2020). Based on a survey of 2279 graduate students (90% Ph.D. and 10% Master's students) from 26 countries Evans et al (2018: 282) found that graduate students were six times more likely to experience anxiety and depression than the general population.…”
Section: Crossing Needles Carrying Yarn---my Fieldwork Storymentioning
confidence: 99%
“…This emotion work is constantly present during and beyond the various stages of doing research but is not often made visible in the work that we publish. Perhaps, this is partially due to the institutional silences and stigmatisation of mental health struggles that permeate academia, particularly as experienced by graduate students (Siegel & Keeler, 2020). Furthermore, emotions are often left out in the reporting of research findings as we worry that it will be taken as signs that a researcher lacks objectivity and mental strength to "make it" as a serious scholar.…”
Section: Crossing Needles Carrying Yarn---my Fieldwork Storymentioning
confidence: 99%
“…The campus atmosphere impacts student engagement and their sense of belonging (Museus & Saelua, 2017). Research suggests that student participation in creating an inviting climate where mental health is acknowledged as a challenge in graduate school can help counter the adverse effects associated with graduate studies (Gray et al, 2017;Siegel & Keeler, 2020). Further, when faculty give students a voice and mental health is a focus within a department, students' research productivity is improved (Beasley et al, 2020).…”
Section: Institutional Climatementioning
confidence: 99%
“…One issue related to mental health in higher education is the stigma associated with mental health disorders and seeking help. Researchers mention stigma as an element that requires specific attention and focused intervention (Xiao et al, 2017;Siegel & Keeler, 2020;Mazurek Melnyk et al, 2020). This theme in the research is an important consideration for institutions given the rising incidence of mental health distress.…”
Section: Institutional Climatementioning
confidence: 99%
See 1 more Smart Citation